2012
DOI: 10.1111/j.1744-7917.2012.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a female‐produced, long range pheromone ofAnoplophora glabripennis(Coleoptera: Cerambycidae)

Abstract: Volatiles from female Asian longhorned beetle (ALB), Anoplophora glabripennis, were evaluated as candidate sex pheromone components. Previous studies on ALB have revealed several antennally active compounds from virgin females; however the origins and activity of these compounds were not apparent and require further investigation. We tested the hypothesis that one or more of the ALB contact sex pheromones is a precursor that undergoes abiotic oxidation to yield volatile pheromone components, and evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 63 publications
3
56
0
Order By: Relevance
“…The authors speculated that attractive VOCs might be formed by natural oxidation of double-bonds of unsaturated CHCs (9). Other volatile oxidation products with similar pheromonal activity were also reported in other species ( Macrocentrus grandii (10), Anoplophora glabripennis (11) and Drosophila melanogaster (12)). Therefore, environmentally mediated production of volatile semiochemicals from CHCs demonstrates that some species exploit seemingly harsh environmental factors in their chemical communication.…”
Section: Introductionsupporting
confidence: 72%
“…The authors speculated that attractive VOCs might be formed by natural oxidation of double-bonds of unsaturated CHCs (9). Other volatile oxidation products with similar pheromonal activity were also reported in other species ( Macrocentrus grandii (10), Anoplophora glabripennis (11) and Drosophila melanogaster (12)). Therefore, environmentally mediated production of volatile semiochemicals from CHCs demonstrates that some species exploit seemingly harsh environmental factors in their chemical communication.…”
Section: Introductionsupporting
confidence: 72%
“…Instead, each macroglomerulus observed here appears to correspond to a similar but diminished counterpart in the opposite sex, perhaps suggesting a conserved olfactory function, but with differing sensitivity or downstream circuitry (e.g., Datta et al 2008). Nevertheless, the male-specific macroglomerulus, coupled with the single male-biased OR, hints at a female-produced sex pheromone: perhaps one or more of the oxidized aldehydes that are associated with virgin females and attractive to males (Wickham et al 2012). Similarly, three receptors were more common in the female transcriptome, and female brains contained a potential macroglomerulus (PVL1).…”
Section: Discussionmentioning
confidence: 99%
“…This mixture, however, shows low efficacy of attraction (<100 specimens over multiple seasons; Meng et al 2014; Nehme et al 2014) compared to that of host VOC/pheromone blends that target related genera such as Monochamus (e.g., >2000 specimens, Allison et al 2012), which suggests that a more optimal mixture or attractant likely remains to be discovered. Female-associated VOCs (Wickham et al 2012), a trail pheromone (Hoover et al 2014), and a putative third component of the male-produced aggregation pheromone (Crook et al 2014) have been recently identified, although their effectiveness in monitoring invasion sites has yet to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds play a role in the prevention of lethal desiccation and protect insects from insecticides and chemical penetration (Hadley, 1981;Blomquist et al, 1987;Lockey, 1988). Cuticular lipids may also be a complex mixture of pheromones (Regnier & Law, 1968;Blomquist & Vogt, 2003;Wickham et al, 2012). Cuticular lipids exhibit certain unique structural characteristics and chemical stability.…”
Section: Introductionmentioning
confidence: 99%